2020
DOI: 10.1093/texcom/tgaa094
|View full text |Cite
|
Sign up to set email alerts
|

Large Postural Sways Prevent Foot Tactile Information From Fading: Neurophysiological Evidence

Abstract: Cutaneous foot receptors are important for balance control, and their activation during quiet standing depends on the speed and the amplitude of postural oscillations. We hypothesized that the transmission of cutaneous input to the cortex is reduced during prolonged small postural sways due to receptor adaptation during continued skin compression. Central mechanisms would trigger large sways to reactivate the receptors. We compared the amplitude of positive and negative post-stimulation peaks (P50N90) somatose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 70 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…In particular, the body sways can be regulated within a small area by reducing the amplitude of the centre of pressure displacement (not recorded in the present study) and increasing its frequency. Such tactile exploration, by changing the pressure onto the ground with the feet, likely contributes to improve the signal-to-noise ratio of sensory cues and to determine the limit of stability (Fabre et al 2021; Latash et al, 2003; Murnaghan et al, 2011). The increase in plantar sole afferents through this strategy could be particularly important in the absence of vestibular information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the body sways can be regulated within a small area by reducing the amplitude of the centre of pressure displacement (not recorded in the present study) and increasing its frequency. Such tactile exploration, by changing the pressure onto the ground with the feet, likely contributes to improve the signal-to-noise ratio of sensory cues and to determine the limit of stability (Fabre et al 2021; Latash et al, 2003; Murnaghan et al, 2011). The increase in plantar sole afferents through this strategy could be particularly important in the absence of vestibular information.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalographic (EEG) activity was recorded continuously from 64 Ag/AgCl surface electrodes embedded in an elastic cap (10-20 system, BioSemi ActiveTwo system: BioSemi, Netherlands). Specific to the BioSemi system, "ground" electrodes were replaced by As in previous studies (Duysens et al, 1995, Fabre et al, 2021Staines et al 2000), the largest responses to foot stimulations were observed at electrode Cz (vertex). The SEPs were recorded at this electrode which overlays the sensorimotor feet regions located on the inner surface of the longitudinal fissure.…”
Section: Electrophysiological Recordings and Analysesmentioning
confidence: 99%
“…For instance, slow adapting afferent fibers (Merkel and Ruffini) are known to decrease their instantaneous firing frequency throughout a sustained stimulus (e.g., normal force exerted on the skin surface) while the rapidly adapting type I and II (Meissner and Pacinian corpuscle) afferents only respond to brisk mechanical transients (Knibestöl, 1975;Vedel and Roll, 1982;Vallbo et al, 1995;Trulsson, 2001;Kennedy and Inglis, 2002). Combining brain imaging and behavioral data, a decreased somatosensory transmission was observed, from the periphery to the cortical areas, this was provoked by skin compression on the foot sole when standing, supporting a heavy weight (Handrigan et al, 2012;Lhomond et al, 2016) or when pressure is increased within a small surface area (Fabre et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that this manipulation is effective, we expected drawing accuracy to be altered similarly in both overpressures conditions as compared to the baseline condition (i.e., natural pen grip). The decrease in the somatosensory evoked potentials (P50N80 SEPs) in response to electric stimulation of the tactile afferents is considered as the neural signature of an attenuated sensory processing (Lhomond et al, 2016: Fabre et al, 2021. According to the seminal study of Desmedt and Robertson (1977), the SEP in response to finger stimulation originates, for the early component (<60 ms), from the primary somatosensory cortex (SI) and is highly representative of the stimulus characteristics (e.g., intensity, frequency).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the plantar sole and the support is essential for determining body orientation in space or more particularly with respect to the support on which the feet are resting (e.g., Morasso and Schieppati, 1999 ; Carriot et al, 2004 ; Mouchnino and Blouin, 2013 ). Tactile receptors embedded within the skin of the foot are able to detect very small changes in force relative to the person's weight when standing motionless (e.g., Morasso and Schieppati, 1999 ; Fabre et al, 2021 ). This allows the brain to identify our balance state prior to gait initiation, for example, even though no other information from visual, vestibular, or proprioceptive origin is present (Mouchnino and Blouin, 2013 ).…”
Section: Introductionmentioning
confidence: 99%